Rancang Bangun Aplikasi Racos (Rapid Correspondence System) Di Kantor Bupati Kampar Berbasis Website - Siregar, Arfansyah; Marwa, Safni; Fiatno, Aris (Journal on Pustaka Cendekia Informatika, 2023)
The purpose of this study was to design and build a website information system for managing incoming and outgoing mail according to current procedures at the Kampar Regent's Office. The system was developed equipped with a unidirectional disposition feature and notification facilities via telegram messages accompanied by a more flexible data format, this system is also equipped with an archive feature that allows the letter search process to be faster when needed, so that the management of letters at the Kampar Regent's Office is more secure, efficient and accurate. The information system discussed in this study is based on a website, this system will be called RACOS (RAPID CORRESPONDECE SYSTEM).The RACOS system was built using the PHP programming language, Laravel Framework and MySQL. For this study, UML (Unified Modeling Leanguage) was used to design applications and the Spiral method in system development.